Investigating the Properties of Foamed Mixture Lightweight Soil Mixed with Bauxite Tailings as Filler. (14th August 2019) - Peng, Yuansheng; Jiang, Jie; Ou, Xiaoduo; Qin, Jinxi
Abstract : To make better use of large amounts of discarded bauxite tailings (BTs), a foamed mixture lightweight soil mixed with BTs as filler (FMLSB) was proposed. Using the orthogonal experimental design method, the effects of various contents of cement, BTs, and foam on the fluidity, wet density, unconfined compressive strength, water absorption, and microstructure of FMLSB were studied. The experimental results indicate that the wet density and unconfined compressive strength increase as the contents of cement and BTs increase but decrease as the foam content increases. Water absorption increases with the reduction of the wet density, but the unconfined compressive strength exponentially increases as the wet density increases. With an increase in the contents of cement and BTs and a decrease in the foam content, fewer pores are present, and the pores are not connected with each other. The results of the range analysis show that the main factor affecting the wet density and unconfined compressive strength of the FMLSB is the foam content, followed by the cement content, and meanwhile, BTs can maintain the lightweight and high strength of FMLSB. Based on the intended engineering applications and standard specifications, the optimum composition of the FMLSB mixture is proposed. Overall, the results indicate that BTs have the potential to be used as filler to produce FMLSB and that applications of FMLSB will lead to great economic and environmental benefits in engineering construction.